Quality of HIV care provided by nurse practitioners, physician assistants, and physicians. - Wilson, Ira B; Landon, Bruce E; Hirschhorn, Lisa R; McInnes, Keith; Ding, Lin; Marsden, Peter V; Cleary, Paul D (Annals of internal medicine, 2005)
Nurse practitioners (NPs) and physician assistants (PAs) are primary care providers for patients with HIV in some clinics, but little is known about the quality of care that they provide.
Keywords: Acquired Immunodeficiency Syndrome; Cross-Sectional Studies; HIV Infections; Humans; Nurse Practitioners; Physician Assistants; Physician's Practice Patterns; Physicians; Quality of Health Care; Selection Bias; United States